Half century of academic production in Capital Market in Brazil in high impact journals - Juliano Lima Pinheiro; Christian Moisés Tomaz; Natália Xavier Bueno; Wendel Alex Castro Silva (BBR: Brazilian Business Review)
This article presents an analysis of the Brazilian scientific research in Capital Markets, from 1961 to 2016, published in journals of high impact in the area of Administration, Accounting and Tourism. We intend to outline a research profile in Capital Markets from journals with A2 impact factor classification according to the Qualis/CAPES list in 2010, as well as the specific periodicals of the area such as RBFin, RBMEC, CE and RC&F. Methodologically, this is an empirical study with bibliometric investigation, longitudinal temporal cross-section, quantitative approach and a statistical non-probabilistic sampling, descriptive regarding the purpose, and documental regarding the means. As main results, capital market articles represented 458 papers (6.12%) of the 7,489 papers published in these journals, produced by 607 authors in 12 different Brazilian scientific journals, emphasizing that the Brazilian production represents only 43% of foreign production, that is, 13,053 articles of 91,684 articles. The RBFin, RC&F, RBMEC and RAE (Print) published, respectively, the majority of the articles, with the RBFin being the journal that stood out with 28% of the scientific production in the studied period. Therefore, the scientific production of Capital Markets appears to be very concentrated in few individuals, in institutions of the southeast and south regions and published, mostly, in specific scientific periodicals.